Mecanismos de votação ao longo dos anos: panorama internacional desde o voto em papel até o uso de tecnologias blockchain - Salmázio, Flávia Caroline Augusto (Universidade Federal de São Carlos, 2025)
The analysis of society through technology is part of the framework studied in Science, Technology, and Society. This research analyzes the scientific knowledge produced in theses and dissertations related to electronic voting. The approaches used are quantitative and qualitative, employing the methods of Bibliometrics and Content Analysis. Through a systematic review of specialized literature, 116 theses and dissertations deposited between 2002 and 2022 in academic repositories in Brazil (50), the United States (60), and Romania (6) were selected and examined, based on specific search terms adapted to each context. For each work, institutional data, authorship, supervision, and year of defense were collected, in addition to conducting content analysis. From the analyses, the emergence of blockchain technology was identified as one of the most relevant trends in contemporary discussions on integrity, transparency, and security in electronic voting. Thus, the analysis was deepened for countries that have already adopted this technology in their electoral processes. Romania, in particular, was the subject of a detailed study for presenting a pioneering and normatively structured system for the use of blockchain in elections, considered a reference in the European context. The Romanian experience was examined based on documentary analysis, such as official documents from the country, specialized literature, and based on international parameters of electoral security. The results indicate that, although the use of blockchain is not yet widespread, its refinement and future application to national elections can offer significant guarantees regarding the traceability and inviolability of electoral data. In this sense, further comparative studies and pilot applications in different national contexts are recommended, with a view to building adaptable, transparent, and technologically secure models using blockchain.
Voting mechanisms throughout the years: an international overview from paper ballots to the use of blockchain technologies
Keywords: votação eletrônica; tecnologia blockchain; integridade eleitoral; ciência, tecnologia e sociedade; sistemas eleitorais; electronic voting; blockchain technology; electoral integrity; science, technology and society; electoral systems; CIENCIAS SOCIAIS APLICADAS; 16. Paz, Justiça e Instituições Eficazes